Implementasi Kebijakan Kawasan Tanpa Rokok (KTR) di Fakultas Ilmu Keolahragaan dan Kesehatan Universitas Negeri Makassar - Nur Inayah Ismaniar; Irwandy Rachman; Samsiana Samsiana; Sri Rezkiani Kas; Meliana Handayani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The implementation of the No Smoking Area is important in the campus environment because the campus is one of the places that should implement the No Smoking Area. In addition, the campus is a place of learning, where people in it are not only people who smoke, but there are also many passive smokers. Student smoking behavior that is carried out every day inside and outside the lecture hall causes the prevalence of cigarette smoke in the campus environment. With several reasons, there are many male students who smoke. This study aims to determine the implementation of the KTR policy by academics within the scope of the Faculty of Sport and Health Sciences, Makassar State University. This research uses a qualitative study design with data collection methods in this study, namely interviews and participatory observation. The results of this study, namely the implementation of academics regarding communication, resources, bureaucratic structure, and disposition towards KTR policies in the FIKK UNM environment become an obstacle to the enforcement of policy compliance. The conclusion of the results of interviews with observations of research variables in the campus environment is not in line in its implementation. It is recommended to the Faculty of Sport and Health Sciences UNM to increase compliance with KTR policies in the campus environment by increasing communication variables, disposition, resources and bureaucratic structures so that it will reduce the prevalence of smoking rates in the campus environment.